PTU-177 Duodenal Adenomas: A Review Of Their Management And The High Risk Of Co-existing Colon Cancer. (9th June 2014) - Chandel, R; Brett, B; Williams, M
Abstract : Introduction: We reviewed the management of Duodenal adenomas at James Paget University Hospital, Great Yarmouth between 2001 and 2013. Methods: 20 patients were included in this study. A standardised proforma was completed for each case and the information was then collated. Results: A CT scan was performed in 13/20 patients. 3/20 had CT and Endoscopic Ultrasound. 4/20 had no imaging. 14/20 patients had Endoscopic Mucosal Resection (EMR). 5/20 had surgery. 1/20 case was monitored with annual surveillance OGDs. 11/14 patients had EMR within 6 months of diagnosis. Complete resection was achieved in 11/14. Argon Plasma Coagulation (APC) was used in 3/14. The American Society of Gastroenterology guidelines 1 recommend routine insertion of prophylactic pancreatic stents for patients undergoing EMR of Ampullary adenomas. 6 of our patients had EMR for Ampullary adenoma and only 1 had a Pancreatic stent inserted. However none of these procedures were complicated by Pancreatitis. 4/14 patients had serious complications following EMR. 3 of these had bleeding from the EMR site while one had a large mucosal defect needing Endoclip application. The 30 day mortality was 0. The frequency of long term follow up was in compliance with the Spigelman scoring system. 5 4/14 patients had recurrent Duodenal adenomas after EMR. Various studies have previously demonstrated a high incidence of co-existing Colorectal neoplasms in patients with sporadic Duodenal adenomas. 2–4 The same was observed in our patients. Of the 17/20 patients who had Duodenal adenomas and intact colons, 11 had a colonoscopy. 3 were found to have Colon cancer, 4 had Colonic adenomas and 1 had hyperplastic polyps. Conclusion: We recommend imaging for all polyps >1 cm. All patients should have EMR within 6 months of diagnosis. Only 1/6 patients who had EMR of ampullary lesions had a Pancreatic stent inserted. None developed Pancreatitis. 4/14 had serious complications following EMR. Long term follow up was in compliance with Spigelman scoring system. 4/14 had recurrent Duodenal adenomas after EMR. 3 patients were found to have Colon cancer. So it is essential that all patients with Duodenal adenomas have a colonoscopy. References: The role of endoscopy in ampullary and duodenal adenomas. Gastrointestinal Endoscopy 2006; 64(6) Murray et al ., Sporadic duodenal adenoma is associated with colorectal neoplasia. Gut 2004 Ramsoekh et al ., Sporadic duodenal adenoma and the association with colorectal neoplasia: a case-control study. The American Journal of Gastroenterology 2008 van Heumen et al ., Management of sporadic duodenal adenomas and the association with colorectal neoplasms: a retrospective cohort study. J Clin Gastroenterol 2012 May Spigelman et al ., Upper gastrointestinal cancer in patients with familial adenomatous polyposis. Lancet 1989 Disclosure of Interest: None Declared.